Community Engagement in Crime Reduction Strategies: A Tale of Three Cities - Linda Nubani; Harmony Fierke-Gmazel; Holly Madill; Alaina De Biasi (Journal of Participatory Research Methods)
Violent crimes in the United States rose for the first time in four years in 2020 (FBI, 2020). The typical and seeming logical response by communities and their police departments is to dispatch more officers to areas of criminal activity. But crime data tracked over the years shows that ‘overpolicing’ isn’t an effective tool at lessening crime rates, can be a strain on budgets, and can heighten tense relationships between police and community members. In this research, we test a community-engaged participatory research approach that combines crime data, design, and engagement in developing the needed policies, tools, and strategies for crime prevention in three medium-sized cities in Michigan. This innovative approach enabled action-oriented recommendations for neighborhood improvements that were grounded in the needs, issues, and concerns of each city. Our data collection approach was an iterative process, whereby data collected at one phase informed data collected in subsequent phases. While our crime data were collected between 2017-2019, our findings showed that bringing residents and stakeholders together with decision-makers and experts can be an effective tool to address environmental design and crime prevention policies especially in the postpolice defunding era. Additionally, successful crime prevention should be based on social programs and physical improvements to the built environment that are unique to the city. In summary, this participatory approach offers non-police driven crime prevention strategies and allows community members an opportunity to drive these strategies.